CONODONTS AND UPPER DEVONIAN (FRASNIAN) BIOSTRATIGRAPHY OF CENTRAL REGIONS OF RUSSIAN PLATFORM - Ovnatanova N.S.; Kononova L.I. (My University, 2001)
The task of this paper is to discuss the Frasnian Stratigraphy of the central region of the Russian Platform; to analyse the distribution of the most abundantly occurring platform conodonts: to revise the zonal schemes earlier developed for the region, and to address the problems related to intra- and interregional correlation. Besides, some comments are presented with regard to Conodont Biofacies. Also, we publish the new Frasnian shallow-water zonal conodont scale and show its correlation with the new Miospore Zonation (AVCHIMOVITCH et al. 1993). The description on is provided for 45 species of Polygnathus, among them 10 newly described species in open nomenclature. Ontogenetic rows for individual species are drawn and intra-Polygnathus phylogenetic links are outlined.
Keywords: Devonian; Frasnian; Conodonts; Russian Platform; Paleozoic::Devonian; Paleozoic::Devonian::Upper::Frasnian; Палеозой::Девонская; Палеозой::Девонская::Верхний::Франский